Pediatric Umbilical Reconstruction : Principles and Techniques - Shiffman, Melvin A. (Springer International Publishing : Imprint: Springer, 2017)
The book starts with a short introduction to the topic, followed by a detailed description of the anatomical differences between exstrophy and gastroschisis. In the following chapters, the authors describe the surgical umbilicoplasty for congenital defects in children. Outcomes and complications will be discussed in the last chapter. Written by respected authors, this book will offer residents and fellows as well as practicing and highly experienced plastic surgeons essential guidance on treatment and decision-making concerning umbilical reconstruction. Its numerous illustrations and clearly structured content make the book a must-read.
Keywords: Medicine.; Pediatric surgery.; Plastic surgery.; elektronické knihy; electronic books